Psychology and Society in Dialogue with Decolonial Feminisms: Perspectives from the global south, Volume 1 - Boonzaier, Floretta; Kessi, Shose; Ravn, Amalie (PINS-Psychology in Society, 2019)
In the call for this special issue we, incoming editors of PINS, expressed the desire to build on the fast-growing legacy and genesis of decoloniality through encouraging and amplifying the most marginalised perspectives and approaches within contemporary decolonial trends. There are a range of reasons why this current moment of decoloniality has energetically re-emerged and taken hold in knowledge production and activist efforts globally. Foremost amongst these reasons is the fact that global inequalities that are racialized, gendered, spatial and classed are rising; and past injustices, and historical and collective traumas, are either completely erased or silenced. Calls for decoloniality have taken hold in the context of ongoing racialized, patriarchal, heterosexist and structural violence.